Ubiquitin-specific peptidase 3 induces TPA-mediated leukemia cell differentiation via regulating H2AK119ub. Issue 5 (3rd September 2019) - Chae, Yun-Cheol; Jung, Hyeonsoo; Kim, Ji-Young; Lee, Dong Ho; Seo, Sang-Beom
ABSTRACT: Acute myeloid leukemia (AML) is the most common type of leukemia in adults. Owing to the chemotherapy associated side effects and toxicity, it is necessary to find a new mechanism, which can identify new potential therapeutic targets at the molecular level. Here, we identified new target genes that are induced during the TPA-induced HL-60 cell differentiation by ChIP-seq and microarray data analysis. Using q-PCR and ChIP assay, we confirmed that the target genes including USP3, USP35, TCF4, and SGK1 are upregulated during TPA-mediated HL-60 cell differentiation. Levels of USP3, one of the deubiquitinating enzymes (DUBs), increased by TPA treatment, resulting in the reduction of H2AK119ub levels. In addition, we revealed that depletion of USP3 inhibits TPA-mediated leukemia cell differentiation q-PCR and FACS analysis. Taken together, our data indicate that USP3 promotes TPA-mediated leukemia cell differentiation via regulating H2AK119ub levels.